Peran Transportasi Online Terhadap Pendapatan Masyarakat dan Perubahan Sosial Ekonomi di Kota Baubau - Hajia, Muhammad Chaiddir (Jurnal Studi Multidisiplin Qomaruna, 2025)
Baubau City is one of the cities in Southeast Sulawesi, with its government system and economic activities, of course transportation is an important component to support the activities of its people. The purpose of the study is to determine the impact of online transportation on the income of drivers or online ojek. The sample in this study was 25 people who were active online ojek, this is because the kururio could not provide data on the number of riders who use online services from kururio. Research was taken using questionnaire filling. The conclusion of this study is that joining Kururio as a partner can affect or increase income. Based on the determination of the score for respondents, the average value obtained is 2.82 which is a good category so that the conclusion is that ojek or online drivers are able to provide guarantees to meet basic daily needs. The suggestion given is that Kurio needs to improve the services provided to partners so that partners can feel a significant impact on income after switching from conventional ojek to ojek or online drivers.